2015
DOI: 10.1371/journal.pone.0133318
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Innate Immunity Contributes to Colonization of the Insect Gut by Yersinia pestis

Abstract: Yersinia pestis, the causative agent of bubonic and pneumonic plague, is typically a zoonotic vector-borne disease of wild rodents. Bacterial biofilm formation in the proventriculus of the flea contributes to chronic infection of fleas and facilitates efficient disease transmission. However prior to biofilm formation, ingested bacteria must survive within the flea midgut, and yet little is known about vector-pathogen interactions that are required for flea gut colonization. Here we establish a Drosophila melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…To our knowledge, this is the first study that directly indicated a potential role of phoP in the survival of Y. pestis within the flea digestive tract. Our results are consistent with the finding in a Drosophila melanogaster model for the Y. pestis colonization of insect vectors that the loss of phoP results in decreased colonization of the midgut of fly larvae (39). Although the mechanism by which phoP promotes bacterial survival in the fleas is unclear, it may be a subtle role that is not easily detected in a single-strain infection assay.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this is the first study that directly indicated a potential role of phoP in the survival of Y. pestis within the flea digestive tract. Our results are consistent with the finding in a Drosophila melanogaster model for the Y. pestis colonization of insect vectors that the loss of phoP results in decreased colonization of the midgut of fly larvae (39). Although the mechanism by which phoP promotes bacterial survival in the fleas is unclear, it may be a subtle role that is not easily detected in a single-strain infection assay.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study reported that Y. pestis lacking other genes in the lipid A modification pathway (galU and arnB) is defective in colonizing the flea midgut (40). In addition, the aforementioned Drosophila model of Y. pestis colonization showed that the decreased colonization of fly larvae by the phoP mutant strain can be rescued by the inactivation of the host imd, the gene that drives the production of antimicrobial peptides (39). Therefore, we cannot rule out the possibility that the lipid A modification and the resistance to antimicrobial peptide play some role in Y. pestis survival in the flea.…”
Section: Discussionmentioning
confidence: 99%
“…; it was identified that Providencia sneebia is lethal while propagating in the fly but elicits a mild immune response (282). Moreover, a chronic gut Yersinia pestis infection was established in the anterior fly larva midgut to mimic and dissect the relationships between biofilm-associated genes (PhoP, GmhA, and OxyR), the gut immune system, and antimicrobial peptides (283).…”
Section: Nonvertebrate Animal Modelsmentioning
confidence: 99%
“…RybB-mediated repression of WaaR could as well contribute to bacterial adhesion and phagocytosis as discussed earlier. Severe defects in LPS or lack of PhoP have been shown to cause defects in colonization, biofilm formation, and sensitivity to antimicrobial peptides in many pathogenic bacteria such as Yersinia pestis [ 83 ].…”
Section: Impact Of Regulated Lps Modifications On Virulence Associmentioning
confidence: 99%